Legal Aspects of House Sales Agreement With Inhouse Method - Dian Yunari; Moh Saleh (Faculty of Law, Merdeka University Surabaya, 2021)
House buying and selling can be performed with cash or installments through bank or KPR/PPR. In addition, a method of buying and selling houses between housing developers and buyers by installments can be also done without mortgage process called inhouse system. The purpose of this study is to determine and analyze the legal aspects of the house sale and purchase agreement using the in-house method. A house sale and purchase agreement and land rights must pay attention to the elements of Article 1320 BW regarding the validity of an agreement. Buyers are required to check the legality of a housing development company and the legality of the housing unit to be built. Prospective buyers are expected not to be tempted by prices far below the housing market price, even though the company offers credit facilities without usury and bank mortgages. It's a good idea for buyers to make transactions if the building has been built, although partly to avoid fraud by the developer. To prevent development companies that do not comply with statutory regulations on settlements, the Regional Government should supervise and enforce the law regarding the legality of housing and infrastructure development, facilities and utilities as well as other environmental permits so that buyers' rights can be fully guaranteed.